Predicting climate-change impacts on the global glacier-fed stream microbiome - Massimo Bourquin; Hannes Peter; Grégoire Michoud; Susheel Bhanu Busi; Tyler J. Kohler; Andrew L. Robison; Mike Styllas; Leïla Ezzat; Aileen U. Geers; Matthias Huss; Stilianos Fodelianakis; The Vanishing Glaciers Field Team; et al. (Nature Communications)
Abstract The shrinkage of glaciers and the vanishing of glacier-fed streams (GFSs) are emblematic of climate change. However, forecasts of how GFS microbiome structure and function will change under projected climate change scenarios are lacking. Combining 2,333 prokaryotic metagenome-assembled genomes with climatic, glaciological, and environmental data collected by the Vanishing Glaciers project from 164 GFSs draining Earth’s major mountain ranges, we here predict the future of the GFS microbiome until the end of the century under various climate change scenarios. Our model framework is rooted in a space-for-time substitution design and leverages statistical learning approaches. We predict that declining environmental selection promotes primary production in GFSs, stimulating both bacterial biomass and biodiversity. Concomitantly, predictions suggest that the phylogenetic structure of the GFS microbiome will change and entire bacterial clades are at risk. Furthermore, genomic projections reveal that microbiome functions will shift, with intensified solar energy acquisition pathways, heterotrophy and algal-bacterial interactions. Altogether, we project a ‘greener’ future of the world’s GFSs accompanied by a loss of clades that have adapted to environmental harshness, with consequences for ecosystem functioning.